Splenic angiosarcoma with hepatic and cardiac metastases: a case report and literature review - Chen, Fangzheng; Zhao, Ding; Yu, Haotian; Wang, Shuai; Wang, Yahao; Lv, Haitao (Frontiers in Oncology, 2025)
Splenic angiosarcoma (SA) is an rare malignant tumor in clinical practice, characterized by high malignancy, atypical early symptoms, and a dismal prognosis. In recent years, growing attention has been focused on its diagnosis and treatment. This report describes a patient who was admitted to the hospital due to left upper abdominal pain. Contrast-enhanced CT indicated unevenly enhanced tumors in the spleen, liver, and right atrium. The patient was treated with laparoscopic splenectomy + partial hepatectomy and was diagnosed based on postoperative pathology and immunohistochemistry (positive for CD31 and CD34). After the operation, anlotinib + toripalimab targeted immunotherapy was used, and the patient recovered well. This case suggests that SA is prone to metastasis in the early stage. Clinically, the diagnosis of SA requires a combination of pathological diagnosis and imaging diagnosis, and postoperative targeted immunotherapy may improve the prognosis.